Guest‐induced Assembly of Bis(thiosemicarbazonato) Zinc(II) Coordination Nanotubes. Issue 29 (23rd March 2017) - Paterson, Brett M.; White, Keith F.; White, Jonathan M.; Abrahams, Brendan F.; Donnelly, Paul S.
Abstract: A Zn II complex of the dianionic tetradentate ligand formed by deprotonation of glyoxal‐bis(4‐phenyl‐3‐thiosemicarbazone) (H2 gtsp) is a [3+3] trinuclear triangular prism. Recrystallization of this complex in the presence of either CO2, CS2, or CH3 CN leads to the formation of [4+4] open‐ended charge‐neutral tetranuclear coordination nanotubes, approximately 2 nm in length and with internal dimensions large enough to accommodate linear guest molecules, which serve to template their formation. Upon removal of the templating molecules the nanotubes demonstrated reversible sorption of CO2 with an isosteric enthalpy of sorption of 28 kJ mol −1 at low loading. Abstract : From three to four : Flexible dianionic bridging ligands and zinc(II) centers form either charge‐neutral triangular prisms or—in the presence of linear templating molecules, CO2, CS2, and CH3 CN—charge‐neutral square coordination nanotubes with the templating agent included as a guest. The template can be removed from the inclusion complex while maintaining a porous material capable of adsorbing roughly two molecules of CO2 per nanotube.